Effectiveness of Mangifera indica L. Leaf Extract in Controlling Candida albicans Growth on Orthodontic Retainers: A Promising Approach to Improve Oral Hygiene - Yuni; Martono; Azzahra Yasmien Siahaan (HM Publisher, 2025)
Background: Orthodontic retainers, especially thermoplastic retainers, are prone to Candida albicans colonization, potentially leading to oral health issues. This study investigated the effectiveness of Mangifera indica L. leaf extract in controlling C. albicans growth on orthodontic retainers and also analyzed its phytochemical constituents. Methods: M. indica leaf extract was prepared using maceration and digestion techniques. Thermoplastic retainers were contaminated with C. albicans and then immersed in different concentrations of M. indica leaf extract (25%, 50%, 75%, and 100%) for 15 minutes. Chlorhexidine digluconate 2% served as the positive control, and dimethyl sulfoxide (DMSO) was the negative control. The antifungal activity was evaluated by measuring the diameter of the inhibition zone. Phytochemical screening was conducted to identify the presence of various secondary metabolites in the extract. Results: All concentrations of M. indica leaf extract demonstrated significant antifungal activity against C. albicans. The 75% extract showed the highest inhibition zone, comparable to chlorhexidine digluconate 2%. Phytochemical screening revealed the presence of alkaloids, flavonoids, tannins, and other bioactive compounds in the extract. Conclusion: M. indica leaf extract, particularly at 75% concentration, effectively inhibits C. albicans growth on orthodontic retainers, suggesting its potential as a natural alternative for maintaining oral hygiene during orthodontic treatment. The presence of various bioactive compounds in the extract contributes to its antifungal activity.